Expert Monitoring Network Plan: Shorebirds - Commitee for Holarctic Shorebird Monitoring (CHASM) (Conservation of Arctic Flora and Fauna (CAFF), 2003)
CAFF CBMP Report No. 4 by the Committee for Holarctic Shorebird Monitoring (CHASM) November 2004 CAFF Designated Agencies: Canadian Wildlife Service, Yellowknife, Canada Finnish Ministry of the Environment, Helsinki, Finland Greenland Homerule, Ministry of the Environment, Nuuk, Greenland Icelandic Institute of Natural History, Reykjavik, Iceland Directorate for Nature Management, Trondheim, Norway Russian Federation Ministry of Natural Resources, Moscow, Russia Swedish Environmental Protection Agency, Stockholm, Sweden United States Fish and Wildlife Service, Anchorage, Alaska A document to describe the goals and preliminary recommendations for the Committee for Holarctic Shorebird Monitoring (CHASM), an expert working group of the Circumpolra Biodiversity Montiroing Program (CBMP.) The Committee for Holarctic Shorebird Monitoring, CHASM, is a “project” within the International Wader Study Group and is one of the Expert Monitoring Networks of the Circumpolar Biodiversity Monitoring Program of CAFF. CHASM was formed as the essential first step for guiding the implementation of an effective circumpolar program for monitoring Arctic-nesting shorebirds. A circumpolar monitoring program will help ensure that existing monitoring programs continue to be well coordinated and supported, while simultaneously integrating them into a Holarctic program.